Peningkatan Keberanian Berpendapat Siswa SD Islam Unggulan Al-Maslachah Sidoarjo melalui Penerapan Model Time Token dalam Pembelajaran Bahasa Indonesia pada masa Covid-19 - Abdul Jamil, Dwi Laili Kirana Putri; Perdana, Parrisca Indra (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
By utilizing the Time Token learning model, this study aims to measure students' courage to voice their opinions. The teacher uses the time token model in an effort to give students a sense of courage to voice their opinions in the hope that it will encourage students to do the same. This research is structured as follows by considering the background of the problem: Can using the time token concept to teach students Indonesian language material can increase students' courage to voice their opinions? At the Al-Maslachah Islamic Elementary School it has been proven that this teaching model can help Class VI children to develop the courage to express their opinions. Classroom Action research method used in this study. From the results of the study and analysis, it can be concluded that the application of the time token learning model in Indonesian language learning can arouse the courage of the sixth grade students of Al-Maslachah Islamic Elementary School, according to the findings of the research and analysis conducted. Therefore, it is recommended that teachers use the Time Token learning model when teaching Indonesian.